Study on 3D-Direct Ink Writing based on adding silica submicron-particles to improve the rheological properties of alumina ceramic ink. (September 2021) - Ye, Zhenyu; Chu, Chengyi; Zhang, Diwei; Ma, Siwei; Guo, Jianjun; Cheng, Yuchuan; Xu, Gaojie; Li, Zhixiang; Sun, Aihua
Abstract: In this report, alumina–silica composite ceramic is manufactured by using the 3D–Direct Ink Writing (DIW) printing technology based on additive manufacturing. In order to improve the compactness and mechanical properties of the alumina ceramics, the silica submicron-particles are introduced as sintering aids and fillers. However, no research has focused on the effect of adding silica submicron-particles on the alumina ceramic manufactured by 3D–DIW. Due to the addition of silica submicron-particles, the upper limit of alumina solids in 3D–DIW ink is increased. Then the effect of silica submicron-particles on the rheological behavior of 3D–DIW ink was studied. In the linear viscoelastic region, the ink with high –solid (75 wt%) with elastic modulus of about 7.5 × 10 5 Pa is the best concentration for 3D–DIW. High–solid ink was used to manufacture 3D alumina–silica composite ceramic parts, and a series of testing methods were used to examine the related properties after sintering at 1600 °C, including volume shrinkage, microstructure and compressive strength. Graphical Abstract: ga1 Highlights: Higher solid content alumina ink was prepared by adding silica nanoparticles. Alumina ceramic structures were generated by 3D direct ink writing. The synergistic effect of silica and alumina particles results in the reduction of the rheological performance of ink.